Morphological biomarkers in the Rhinocricus padbergi midgut exposed to contaminated soil - Souza, Tatiana da Silva [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Morphological studies have been performed in invertebrates to elucidate cellular and/or tissue damage caused by environmental contamination. In present work, the exposure to industrial soil contaminated with polycyclic aromatic hydrocarbons and metals led to histological alterations in the midgut of Rhinocricus padbergi (Diplopoda). The following alterations were observed: increase of cytoplasmic granules in the fat body; increase in the number of regions of the epithelium in the process of renewal; increase in the number of hemocytes present among the cells of the fat body and degenerative changes in the midgut epithelium. Based on the results, we concluded that R. padbergi proved to be an excellent bioindicator for the evaluation of soil quality. The observed changes could be used as biomarkers for assessing sublethal effects of contaminated soils. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Histopathology; Ecotoxicology; Landfarming; Heavy metals; PAHs